THE UNIQUE OPPORTUNITIES OF ACCOUNTING TO PROMOTE TRANSPARENCY OF ECONOMIC PROCESSES - Slyozko, Tetyana; Kurilo, Lyudmila; Mazina, Oleksandra (Copernican Journal of Finance & Accounting, 2019)
The article is devoted an important role the Institute of Accounting in the modern economy. This role is supported by unique institutional and informational opportunities determined by its specific characteristics. On the one hand, accounting is the legislative and normative institution through which the controlling and regulating institutions influence the economic processes occurring at each enterprise. On the other hand, the accounting system creates an information database on the actual economic activity of each enterprise required by users. Such a database is formed due to the fact that accounting is an exclusive registrar of business activities: documentation, inventory, assessment, calculation, accounts, double-entry bookkeeping, balance, reporting. These methods have such a mathematical feature that has made it possible to fully them with the latest information technologies. All of these factors allow accounting to provide transparent accounting information to any users and institutions.